Exploring the mediating of transformational leadership. Emotional intelligence on civil servants performance - Rumaropen, Alfonsina (Advances in Social Sciences Research Journal, 2019)
The success of a government bureaucracy is largely determined by the ability of state civil apparatus to use emotional intelligence effectively, this effective attitude will increasingly produce results that are in line with expectations if supported by a good leadership style and continuously displayed by superiors. This study explores the contribution of the emotional intelligence on civil servants performance with the support of transformational leadership in 54 people of the civil servants who’s working at the Forestry Office in South Sulawesi Provincial. Testing hypotheses using by Partial Least Square (SEM-PLS) through Smart PLS 3.0 provides evidence that emotional intelligence directly has a positive significant effect on transformational leadership and civil servants performance. Transformational leadership directly has a positive significant effect on civil servants performance. Emotional intelligence has a positive significant effect on civil servants performance with the mediating effect of transformational leadership. Transformational leadership is not proven as a mediating effect in analyzing the effect of emotional intelligence on civil servants performance